The omnichannel effects on fast food service quality and customer experience - Anisa Salsabilla; Siti Rahayu; Fitri Novika Widjaja (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
Digital transformation has reshaped the fast-food industry, where omnichannel strategies integrate online and offline touchpoints to enhance customer experiences. This study examines the impact of omnichannel implementation on service quality, perceived value, and customer satisfaction within Indonesia’s fast-food sector. Using a quantitative design and data from 305 valid respondents, analysed using PLS-SEM (SmartPLS 4.0), the results showed that omnichannel integration significantly improves service quality and perceived value; consequently, customer satisfaction increases. However, the direct effect of omnichannel on satisfaction is insignificant, indicating that the relationship is entirely mediated by service quality and perceived value. These findings confirm the Service-Dominant Logic framework, suggesting that seamless cross-channel experiences co-create value and strengthen customer trust. This study enriches the digital service marketing literature by clarifying how omnichannel performance influences consumer perceptions and by offering managerial insights to enhance cross-platform service consistency.